Endoscopic medial maxillectomy for sinonasal inverted papilloma - Thapa Chettri, Shyam; Karki, S; Shah, SP; Sah, BP; Manandar, S; Kandel, D; Mishra, S; Jaiswal, RK; Panthi, N (Journal of BP Koirala Institute of Health Sciences, 2018)
Background: Traditionally, medial maxillectomy was performed through lateral rhinotomy or mid facial degloving approach for inverted papilloma. Endoscopic medial maxillectomy, since reported first in 1992, has advanced tremendously and has been advocated by a number of authors for the fact that it prevents the morbidity of open approach with a similar recurrence rate. We present our experience of endoscopic medial maxillectomy for sinonasal inverted papilloma.Aims and Objective: To highlight the treatment of inverted papilloma through transnasal endoscopic approach.Methods: This study is a retrospective chart review of 18 patients out of 23 patients of which 5 were lost on follow-up with inverted papilloma who were treated during the last 2 years. Preoperative diagnosis was made on histopathological examination and Krouse staging in CT scans of paranasal sinus was used to estimate the extent of the disease. Then, surgical approach was decided. Post-operative follow up was done by performing direct nasal endoscopy. All patients were followed up for a minimum period of 1 year.Results: Among the 18 patients who underwent endoscopic medial maxillectomy, sex (male : female) ratio were 1.25: 1, age ranged from 24 yrs to 69 yrs with average being 41.7 yrs. According to Krouse staging, 2 patients were in Stage I, 9 patients in Stage II and 7 patients in Stage III. The laterality of the lesion was more on the right. The commonest site of attachment was found to be the lateral wall of nose. The average duration of hospital stay was 4 days. The commonest complication was nasal crusting and the recurrence rate was 11.11%.Conclusion: This work confirms the results described in recent literature and further supports transnasal endoscopic surgery to manage inverted papilloma.Journal of BP Koirala Institute of Health Sciences, Vol. 1, No. 1, 2018, Page: 20-24